Phytochemical and Bioactivity Analysis of Colebrookea oppositifolia Sm. from Nepal's Upper Hills - G.C., Bimal; Ojha, Indra; Basnyat, Ram Chandra; Sharma, Khaga Raj (Journal of Nepal Chemical Society, 2025)
Traditional medicine has long utilized herbal medicine to treat a wide range of illnesses. The purpose of this work was to quantify the levels of flavonoids and phenolic compounds in various solvent extracts and to analyze their antioxidant and antibacterial properties. Ethanol had the higher total flavonoid content (TFC) at 10.58 ± 0.002 mg QE/g and total phenolic content (TPC) at 142.88 ± 0.06 mg GAE/g among the extracts tested. The methanolic extract exhibited stronger antioxidant activity compared to the ethanolic extract, with an IC50 of 10.34 ± 2.31 µg/ml. Both methanolic and ethanolic extracts effectively inhibited Staphylococcus aureus, showing a zone of inhibition of 15 mm and 16 mm, respectively, which is nearly closer to the positive control, neomycin (22 mm), according to antibacterial testing. In contrast to the control (0.0152 mg/mL and 0.0313 mg/mL), the methanolic extract displayed significant minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values against Staphylococcus aureus (12.5 mg/mL and 25 mg/mL, respectively). These results indicate that the examined plant extracts possess substantial bioactive potential, particularly the methanolic and ethanolic extracts, making them promising sources for the isolation of active compounds that could be drug candidates in the future drug development process against infectious diseases.